Pengaruh Pertumbuhan Ekonomi Dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan Masyarakat - Vitriani, Nur; Selvia, Riska (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Poverty reduction is a serious issue for countries around the world, including Indonesia as a developing country that makes poverty reduction one of the targets in national development. This research is quantitative in nature with the data used is secondary which is presented in the form of time series data for 4 years, from 2021 to 2024. This research focuses on the city of Lampung. The type of data used is secondary data obtained from the Central Statistics Agency (BPS) website. The results of this study indicate that economic growth has a positive but insignificant effect on poverty, while the open unemployment rate has a negative and insignificant effect on poverty.